Improving Compliance towards International Humanitarian Law: Filling in the Gaps? - Hamidah, Fitry Nabiilah; Muhammadin, Fajri Matahati (Al-Daulah : Journal of Criminal Law and State Administration Law, 2024)
Research Objective: This study evaluates existing International Humanitarian Law compliance mechanisms, identifies implementation gaps, and assesses factors influencing adherence by states and non-state armed groups in conflict situations. Research Methodology: The research employs qualitative methodological approaches through case study analysis and comprehensive literature review to systematically evaluate IHL compliance mechanisms and factors affecting adherence. Results: The research identifies deficiencies in IHL enforcement systems, cultural barriers to implementation, and limitations in engaging non-state actors as primary impediments to compliance. Findings and Implications: The findings demonstrate systemic enforcement deficiencies, cultural impediments, and limited non-state actor engagement hindering effective IHL implementation, implying the need for more holistic approaches to enhance compliance across diverse conflict contexts. Conclusion: Despite providing a comprehensive legal framework to protect civilians during armed conflicts, persistent non-compliance undermines IHL's effectiveness and credibility, necessitating a multidisciplinary approach addressing legal, political, cultural, and operational factors. Contribution: This research contributes by advocating multidisciplinary approaches to enhance compliance, proposing implementation strengthening mechanisms, highlighting stakeholder roles, and developing a conceptual framework for holistic compliance systems. Limitations: From an academic perspective, the qualitative methodology employed presents inherent limitations in statistical generalizability. The absence of quantitative metrics makes it difficult to measure compliance levels objectively across different contexts. Additionally, case study approaches, while providing depth, naturally restrict the breadth of analytical scope, potentially overlooking unique implementation dynamics in unexamined conflict scenarios. Suggestions: The study recommends establishing permanent platforms for regular IHL discourse, enhancing institutional support, integrating cultural sensitivity, strengthening Red Cross/Red Crescent societies, involving NGOs in IHL dissemination, and facilitating stakeholder interactions. Future research should expand empirical scope through quantitative analyses and broader case studies